Design of Composite Electrodes with Anion-Absorbing Active Materials. Issue 1 (1st January 2017) - Thomas-Alyea, K. E.; Aryanpour, M.
Abstract : Organic radical polymers (ORP) and conjugated polymers provide exceptional rate capability as cathode materials for lithium-ion batteries, albeit low volumetric energy density. To optimize overall power and energy density, we consider a composite of ORP with oxide cathode. Upon charge (oxidation), ORP absorb anions from the electrolyte, which causes the salt content in the cell to decrease during charge. Even if the ORP is only 10 volume% of the cathode, the cell's salt content will decrease by >0.6 M in practical cell designs. Furthermore, the conductivity of typical electrolytes varies strongly with concentration. We use electrochemical modeling of a composite positive electrode containing both lithium-releasing and anion-absorbing active materials to explore the tradeoffs and design implications among salt concentration, porosity, and volume fraction of ORP.